1999
DOI: 10.1590/s0001-37141999000400005
|View full text |Cite
|
Sign up to set email alerts
|

Some enzymatic properties of cholesterol oxidase produced by Brevibacterium sp

Abstract: In this study we determined some properties of the cholesterol oxidase from a Brevibacterium strain isolated from buffalos milk and identified the cholesterol degradation products by the bacterial cell. A small fraction of the enzyme synthesized by cells cultured in liquid medium for 7days was released into the medium whereas a larger fraction remained bound to the cell membrane. The extraction of this fraction was efficiently accomplished in 1 mM phosphate buffer, pH 7.0, containing 0.7% Triton X-100. The enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Some microorganisms were effectively produced cholesterol oxidase based on the temperature. The optimum temperature for this enzyme production Rhodoccococus equi was at 47°C and Corynebacterium cholesterolicum production of this enzyme was at 40°C respectively (Salva et al, 1999). Streptomyces fradiae and Brevibacterium sp.…”
Section: Resultsmentioning
confidence: 92%
“…Some microorganisms were effectively produced cholesterol oxidase based on the temperature. The optimum temperature for this enzyme production Rhodoccococus equi was at 47°C and Corynebacterium cholesterolicum production of this enzyme was at 40°C respectively (Salva et al, 1999). Streptomyces fradiae and Brevibacterium sp.…”
Section: Resultsmentioning
confidence: 92%
“…and have shown that detergent is required for the extraction of ChOx and the activity depends on the concentration of detergent (Triton X-100). They have brought out that enzyme loses its complete activity at 0% concentration of detergent (Salva et al, 1999). Gadda et al have characterized cholesterol oxidase and have studied the effect of detergent, alcohol and phosphate upon ChOx activity.…”
Section: Cholesterol Oxidasementioning
confidence: 99%
“…Cholesterol oxidase (COD; EC 1.1.3.6), is a bifunctional enzyme, which catalyzes the oxidation of cholesterol (5-cholesten-3-ol) to the temporary intermediate 5-cholesten-3-one with the reduction of molecular oxygen to hydrogen peroxide, and the isomerization of the Δ 5 -bond to Δ 4 -bond (4-cholesten-3-one) (Salva et al, 1999;Yamashita et al, 1998). It was observed that there is an increase in cardiovascular diseases and cardiac arrest is a major cause of death all over the world (Davisa et al, 1995).…”
Section: Introductionmentioning
confidence: 99%